Wet cake filtration : fundamentals, equipment, and strategies - Anlauf, Harald (Wiley-VCH, 2019)
Guides readers through the entire process of liquid filtrations, from a basic understanding and lab scale testing to advanced process applications and up-scaling of processes. Wet Cake Filtration is a key method in solid-liquid separation and plays an important role in many industrial processes from the separation of solid products from a liquid, to removing contaminants in wastewater treatment.
Includes index.
Keywords: Filters and filtration.; elektronické knihy; electronic books